IMPACT OF WHOLE BRAIN TEACHING BASED INSTRUCTION ON ACADEMIC PERFORMANCE OF GRADE 8 STUDENTS IN ALGEBRA: COMPENDIUM OF WBT-BASED LESSON PLANS - Sontillano, Raisa D (PUPIL: International Journal of Teaching, Education and Learning, 2018)
Improving students’ academic performance requires the teacher’s knowledge on different classroom instructions based upon how the brain gathers and stores knowledge. One classroom instruction that engages different parts of the brain in an active instructional setting is a method known as Whole brain teaching. This study was conducted to determine the impact of Whole brain teaching or WBT on academic performance of grade 8 students in Algebra. Quasi-experimental research method, specifically, pretest-posttest with control group using matched- subject design was employed in the study. Two heterogeneous classes were randomly selected and assigned as experimental and control groups. Pretest and posttest were used in measuring the academic performance of the students. The experimental group received instructions using WBT techniques whereas the control group underwent the same pacing and content using conventional teaching techniques. Based on the data gathered, the students’ academic performance increased significantly after subjecting them to WBT techniques and conventional teaching techniques. However, results of the posttest comparison of both groups showed that there was a statistically significant difference between the academic performance of experimental and control groups in favor of the experimental group. Thus, Whole brain teaching has a positive impact on academic performance of grade 8 students in Algebra.